TERT regulates telomere-related senescence and apoptosis through DNA damage response in male germ cells exposed to BPDE in vitro and to B[a]P in vivo. (April 2018) - Ling, Xi; Yang, Wang; Zou, Peng; Zhang, Guowei; Wang, Zhi; Zhang, Xi; Chen, Hongqiang; Peng, Kaige; Han, Fei; Liu, Jinyi; Cao, Jia; Ao, Lin
Abstract: Increasing evidence shows that impaired telomere function is associated with male infertility, and various environmental factors are believed to play a pivotal role in telomerase deficiency and telomere shortening. Benzo[ a ]pyrene (B[ a ]P), a ubiquitous pollutant of polycyclic aromatic hydrocarbons (PAHs), can act as a reproductive toxicant; however, the adverse effect of B[ a ]P on telomeres in male reproductive cells has never been studied, and the related mechanisms remain unclear. In this study, we explored the effects of benzo[ a ]pyrene-7, 8-dihydrodiol-9, 10-epoxide (BPDE), the active metabolite of B[ a ]P, on telomere dysfunction in mouse spermatocyte-derived cells (GC-2) and also the potential role of telomerase in BPDE-induced spermatogenic cell damage. The results showed that BPDE induced cell viability inhibition, senescence, and apoptosis in GC-2 cells in a dose-dependent manner. Shortened telomeres, telomere-associated DNA damage, reduced telomerase activity, and TERT expression were also observed in BPDE-treated cells, accompanied with the activation of DNA damage response pathway (ATM/Chk1/p53/p21). Moreover, by establishing the TERT knockdown and re-expression cell models, we found that TERT regulated telomere length and the expression of DNA damage response-related proteins to influence senescence and apoptosis in GC-2 cells. These in vitro findings were further confirmed in vivo in the testicular cells of rats orally administrated with B[ a ]P for 7 days. B[ a ]P treatment resulted in histological lesions, apoptosis, and senescence in the testes of rats, which were accompanied by shortened telomeres, reduced levels of TERT protein, and increased expression of DNA damage response-related proteins. In conclusion, it can be concluded that TERT-mediated telomere dysfunction contributes to B[ a ]P- and BPDE-induced senescence and apoptosis through DNA damage response in male reproductive cells. Graphical abstract: Image 1 Highlights: BPDE treatment triggers senescence and apoptosis, and activates DNA damage response in GC-2 cells. BPDE induces telomere dysfunction and TERT inhibition in GC-2 cells. TERT-mediated telomere dysfunction contributes to BPDE-induced senescence and apoptosis in vitro. B[ a ]P exposure results in testicular toxicity in rats, accompanied by telomere dysfunction of spermatogenic cells. Abstract : TERT mediates B[ a ]P- and BPDE-induced spermatogenic cell damage.